Ketorolac Tromethamine for Sustained Ocular Delivery; Novel In-Situ Gels Development and Evaluation - Kumar, Rohit; Sharma, Vandana; Sharma, Mukesh; Soni, S. L (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Ophthalmic ketorolac is used to treat itchy eyes caused by allergies. It also is used to treat swelling and redness (inflammation) that can occur after cataract surgery. Ketorolac is in a class of medications called nonsteroidal anti-inflammatory drugs (NSAIDs). Methods: Ocular bioavailability is always poor from conventional ophthalmic drops due to spillage and nasolachrymal drainage. Ocular in situ gels can increase the drug residence time thus increasing bioavailability. Polyacrylic acid (Carbopol 934) was used as the gelling agent in combination with hydroxypropylmethylcellulose (Methocel K4M) which acted as a viscosity enhancing agent. Compatibility studies of the drug excipients were carried out using differential scanning calorimetry. The prepared formulations were characterized for clarity, pH, drug content, sol-to-gel transition by scanning electron microscopy, in-vitro and in-vivo drug release, ocular irritation and stability. Results: FTIR spectras revealed that, there was no interaction between LEV and excipients. The formulated gels were transparent, uniform in consistency and had spreadability with a pH range of 7.1 to 7.4. Rheological studies revealed that the formulations were psuedoplastic in nature, drug content of sterile in situ gels was found to be 92-98%.Release kinetic study showed that the formulation followed first order diffusion controlled and the optimized formulations was having good antibacterial efficacy. Conclusion: The said promising formulation (F4) would be able to offer benefits such as increase residence time, prolonged drug release, reduction in frequency of administration and thereby definitely prove to improve the patient compliance.